Literature Study of Lean Implementation Framework for Small and Medium Enterprises (SMEs) in Indonesia - Fatma Nadia Amin; Putu Dana Karningsih (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2020)
Many companies in developed countries are implementing lean manufacturing and offering significant results. However, experts argue that the concept can not only be used in large companies but also in SMEs. Some SMEs in the world have also implemented the lean concept, but there have been many failures during implementation. This is because of the lean implementation framework. Several researchers have developed specific frameworks for lean implementation in SMEs. Therefore the final objective of this study is a lean implementation framework that is suitable for SMEs in Indonesia. In this research, the first step of the literature study is to search for previous studies on google scholar, emerald, elsevier, etc. related to the lean framework. Furthermore, comparing and comparing the framework in previous research. This comparison can be a lean implementation in Indonesia, with the strengths and weaknesses of each of these frameworks